The Efficacy of Intraoperative Passive Language Mapping for Glioma Surgery: A Case Report - Kanaya, Kohei; Mitsuhashi, Takumi; Kiuchi, Takafumi; Kobayashi, Sumio (Frontiers in Neurology, 2021)
Background Recently, electrocorticographic (ECoG) studies have emphasized the importance of gamma band-based functional mapping in the presurgical localization of the eloquent cortex. Passive functional mapping using ECoG signals provides a reliable method for identifying receptive language areas without many of the risks and limitations associated with electrical cortical stimulation. We report a surgical case of left temporal malignant glioma with intraoperative passive language mapping. Case description A 78-year-old woman was diagnosed with left temporal glioma with inspection of her language difficulty. MRI showed a left temporal tumor measuring 74.6 × 50.0 × 51.5 mm in size. Real-time CortiQ-based mapping using high-gamma activity by word-listening and story-listening tasks was performed. Significant listening task-evoked high gamma activities were detected in 5 channels in the superior temporal gyrus and one channel in the middle temporal gyrus. The tumor was grossly removed except for the region corresponding to listening task-evoked high gamma activities. Postoperatively, the patient’s symptoms of language comprehension difficulty improved, and no new neurological deficits were observed. Conclusion Intraoperative passive language mapping was successfully performed, and the patient’s language function was well preserved. Intraoperative passive language mapping, which is applicable in a short time and under general anesthesia, can be an important tool for detecting language areas.